Code-switching between informal Iraqi dialect and English language among Iraqi Arab speakers via WhatsApp application: linguistic and non-linguistic factors - Sabti, Ahmed Abdulateef; Md Rashid, Sabariah; Turki, Hutheifa Yousif (Universiti Putra Malaysia Press, 2019)
Code-switching is described as the shifting that occurs between two or more languages concurrently within one conversation. This study aims to examine the application of code-switching between Informal Iraqi Dialect (IID) and English language among Iraqi Arab speakers of English via one of the smartphone applications, namely WhatsApp Messenger (WM). The study also seeks to recognize the types of code switching and motivations among Iraqi students of English for switching from IID into English language. This research adopted a qualitative approach, which involved Fifty (50) typed conversations of twenty (20) Iraqi post-graduate students studying at Universiti Putra Malaysia (UPM). Data were collected via two instruments, dubbed WM application to gather the typed conversations and semi-structured interviews. The results obtained from the WM application indicated that the most predominant type of code-switching (CS) used by the participants was intra-sentential CS, especially the intra-lexical code-switching. The findings suggest that the majority of the Iraqi students are inclined to code-switch to English language in smaller parts within the word boundary. The analysis of the interview data disclosed three motivations for the application of code-switching, namely linguistic, technological, and political factors.